AIE-active smart cyanostyrene luminogens: polymorphism-dependent multicolor mechanochromism. Issue 2 (15th December 2017) - Yang, Wei; Liu, Chunlin; Lu, Shuang; Du, Jinya; Gao, Qingyun; Zhang, Ronghua; Liu, Yi; Yang, Changying
Abstract : Multicolor-changing mechanochromic characteristics of AIE cyanostyrene luminogens were ascribed to diverse molecular packing modes. Abstract : Multicolor mechanochromic luminescent (MCL) materials are promising candidates in fundamental science and practical applications. In this paper, a series of novel smart luminescent compounds based on a cyanostyrene unit, NAIF, NA-15C5, NAPM, NAIP andNAPF, have been developed.NAIF, NAPM, NAPF andNAIP all exhibit aggregation-induced emission (AIE) characteristics and individually show red, orange, yellow and green emission in their aggregated state. LuminogensNA-15C5 andNAPM display reversible tricolor-changing MCL behaviors.NAIF andNAIP show bicolor switching mechanochromic phenomena. Additionally, different molecular packing modes of two crystalline polymorphs, NAPM- y andNAPM- o with bright yellow and orange luminescence color, rationally explain the tricolor-changing mechanochromic mechanism. Moreover, luminogenNAIP can be used as ink-free rewritable paper.